The Quantumness in Detecting Electromagnetic Waves is Determined by the Interaction Properties of the Detector - C. Roychoudhuri; N. Prasad; G. Fernando (Fundamental Research and Application of Physical Science Vol. 3, 2023)
Einstein’s 1905 paper on the photoelectric effect successfully modeled the published data while explicitly defining light as “indivisible light quanta”. One of the key successes of Quantum Mechanics (QM) of 1925-26, is the release of discrete packet of energy hv during any quantum level transitions in atoms and molecules. These two modern successes have overturned the mathematical and experimental knowledge developed over several centuries behind the optical science and engineering, without successfully bridging the knowledge gap epitomized by the still unresolved “wave-particle-duality” (WPD). Note that, optical science and engineering fields are still thriving using Huygens-Fresnel diffraction integral (HF-DI) of 1817 and Maxwell’s wave equations of 1876, without any controversy. This chapter resolves this dichotomy by eliminating the need for WPD. We provide a model for the atomic emission as a discrete packet of energy hv, as required by QM, but which evolves and propagates out as a Maxwellian classical exponential wave packet, while diffractively spreading out obeying the HF-DI. The continuing need to accept the magical WPD arises because we have not been systematically and explicitly exploring the two-step physical processes which take place during light-detector interaction before the photoelectric data is generated by our apparatus. The two steps are: (i) Linear amplitude-amplitude stimulation induced on the detecting dipoles by the light wave vector; (ii) which is then followed by the quadratic energy absorption step by the detector. If the detector is an LCR oscillator (for radio waves), or an old fashioned Bolometer (for higher frequencies), we would not observe any quantumness in the data. But, when we use a modern quantum photodetector using higher frequency EM waves, we can count highly amplified current pulses of electrons, generated out of each one of the released electron, bound quantum mechanically inside the detector.